WEBINAR & FOCUS GROUP DISCUSSION PENDIRIAN PRODI BISNIS DIGITAL SUATU KAMPUS - Setyawan, Ignatius; Hapsari, Claudia Gita (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2024)
After conducting a series of preparatory meetings in October and November 2023, the PKM implementation method was carried out using the webinar and Focus Group Discussion (FGD) methods. The activity was carried out online via Zoom on November 17, 2023 at 01.00-04.30 PM. This PKM activity was also broadcast live on Youtube. This activity was attended by more than 100 students and more than 10 lecturers from the Faculty of Business Management, Respati Indonesia University (FMB URINDO) who were interested in developing a new study program in the field of digital business. In the FGD session, the PKM team and the FMB URINDO lecturer team managed to reach a common view on 4 important things in establishing a digital business study program. These four important things are graduate profiles, lecturer profiles, curriculum structure, and study materials. Graduate profiles include young entrepreneurs, business consultants & marketing professionals. The lecturer profiles include: academics in the fields of business and IT and experienced as practitioners in the e-commerce industry and product marketers. The curriculum structure includes IMTI and mandatory courses with a minimum total of 144 credits according to the DIKTI SN standard and there is an MBKM scheme. Study materials include several examples of Syllabus for IoT, Fintech, Digital Business Ethics, Digital Business Simulation & Mentoring & Digital Marketing courses. ABSTRAK Setelah melakukan rangkaian rapat persiapan pada bulan Oktober dan November 2023, metode pelaksanaan PKM dilangsungkan dengan menggunakan metode webinar dan Focus Group Discussion (FGD). Kegiatan tersebut dilakukan secara daring melalui media Zoom pada tanggal 17 November 2023 pukul 13.00-16.30 WIB. Kegiatan PKM ini juga ditayangkan di Youtube secara live. Kegiatan ini dihadiri oleh lebih dari 100 mahasiswa dan lebih dari 10 dosen Fakultas Manajemen Bisnis Universitas Respati Indonesia (FMB URINDO) yang tertarik untuk mengembangkan prodi baru di bidang bisnis digital.. Dalam sesi FGD, tim PKM dan tim dosen FMB URINDO berhasil mencapai kesamaan pandangan tentang 4 hal penting dalam pendirian prodi bisnis digital. Keempat hal penting ini adalah profil lulusan, profil dosen, struktur kurikulum, dan bahan kajian. Profil lulusan meliputi wirausahawan muda, konsultan bisnis & profesional pemasaran. Untuk profil dosen meliputi: akademisi bidang bisnis dan IT serta berpengalaman sebagai praktisi bidang industri e-commerce dan pemasar produk. Struktur kurikulum ada mata kuliah inti dan wajib denga total sks minimum 144 standar SN DIKTI dan ada skema MBKM. Bahan kajian meliputi beberapa contoh silabus mata kuliah IoT, Fintech, Etika Bisnis Digital, Simulasi & Mentoring Bisnis Digital & Pemasaran Digital.